CONCURRENT INFECTION OF TETRAMERES SP. AND ECHINOSTOMA SP. IN NOMADIC DUCKS FROM THANJAVUR REGION OF TAMIL NADU - A. Latchumikanthan; E. Tamileniyan; M.K. Vijayasarathi; K. Thilagavathi; R. Velusamy; A. Meenakshisundaram (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Free range grazing ducks play a major role in rural economy of Asian countries in the form of meat and egg production. The present study reports a mixed infection of Tetrameres sp. and Echinostoma sp. in nomadic ducks from Orathanadu, Thanjavur district of Tamil Nadu, India. On post-mortem examination of two ducks with a history of enteritis revealed bright red nematodes in the proventricular mucosa and minute flukes in small intestine. Tetrameres sp. and Echinostoma sp. worms were identified based on morphological characteristics. Intestinal contents also revealed eggs of Tetrameres sp. and Echinostoma sp. Further snails were collected from the duck rearing areas and confirmed the release of Echinostome cercariae and the snails were also identified as Planorbis sp. The study emphasizes the significance of mixed helminthic infections in nomadic ducks from Thanjavur, Tamil Nadu.